2018
DOI: 10.1128/aac.01299-18
|View full text |Cite
|
Sign up to set email alerts
|

In VitroAntiviral Activity of Cabotegravir against HIV-2

Abstract: We examined the antiviral activity of the integrase inhibitor (INI) cabotegravir against HIV-2 isolates from INI-naive individuals. HIV-2 was sensitive to cabotegravir in single-cycle and spreading-infection assays, with 50% effective concentrations (ECs) in the low to subnanomolar range; comparable results were obtained for HIV-1 in both assay formats. Our findings suggest that cabotegravir should be evaluated in clinical trials as a potential option for antiretroviral therapy and preexposure prophylaxis in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 70 publications
1
10
0
Order By: Relevance
“…As previously reported for HIV-1, replacements G140S/Q148H in HIV-1 NL4-3 integrase conferred low-level (2.0-fold) resistance to bictegravir (33,39,51), whereas the T97A/ Y143C mutant did not show resistance to the drug (33) ( Table 3). In addition, the combination of E138K/G140S/Q148R in HIV-1 NL4-3 , which conferred 10-fold resistance to cabotegravir in our previous study (22), yielded a modest increase in the EC 50 for bictegravir (2.3-fold) ( Table 3).…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…As previously reported for HIV-1, replacements G140S/Q148H in HIV-1 NL4-3 integrase conferred low-level (2.0-fold) resistance to bictegravir (33,39,51), whereas the T97A/ Y143C mutant did not show resistance to the drug (33) ( Table 3). In addition, the combination of E138K/G140S/Q148R in HIV-1 NL4-3 , which conferred 10-fold resistance to cabotegravir in our previous study (22), yielded a modest increase in the EC 50 for bictegravir (2.3-fold) ( Table 3).…”
mentioning
confidence: 76%
“…All drug susceptibility measurements were performed using our established MAGIC-5A indicator cell assay, which quantifies drug-dependent inhibition in a single round of HIV infection (35). We previously showed that the results obtained with this assay are concordant with those seen in spreading infections of immortalized T-cell lines, as demonstrated for the INIs raltegravir (17), dolutegravir (21), and cabotegravir (22). In addition, other groups have used similar single-cycle assays to quantify the activity of various INIs against HIV-1 and simian immunodeficiency virus (SIV) (33,(36)(37)(38)(39)(40).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Particularly, in the absence of protective vaccines against HIV-1 46 , 47 , effective long-acting ART not only are the best approaches for PrEP 47 but also could serve as a vaccine-mimetic if dosing intervals are extended to yearly or longer. Moreover, CAB’s activities against HIV-2 provides real potential for dual treatment 48 , 49 . Altogether, we conclude that a major extension of the dosing interval could allow NM2CAB to be developed as a vaccine-mimetic.…”
Section: Discussionmentioning
confidence: 99%
“…A study on integrase inhibitor‐naïve population was conducted to determine the antiviral activity of CAB against HIV‐2. The findings showed that HIV‐2 was sensitive to CAB and suggested that CAB could be a potential ART in PrEP for HIV‐2 …”
Section: Integrase Inhibitormentioning
confidence: 99%